Liberation of metal clads of waste printed circuit boards by removal of halogenated epoxy resin substrate using dimethylacetamide - Verma H.R.; Singh K.K.; Mankhand T.R. (My University, 2025)
Present work reports the evaluation of dimethylacetamide (DMAc) as a solvent to dissolve the halogenated epoxy resin substrate (HERS) of waste printed circuit boards (WPCBs). Studies revealed that HERS dissolution attributes to the cracking and delamination of WPCB's layers. Variation of the parameters governing the dissolution elucidated that dissolution is directly dependent on temperature and WPCBs concentration in DMAc. The results also showed that increase in the WPCBs size drastically retards the rate of HERS dissolution. After delamination, the spent DMAc was regenerated, and the dissolved HERS was recovered as residue. The chemical structure of regenerated solution and recovered residue were found to be similar to pure DMAc and untreated HERS, respectively. Cyclic usage of regenerated DMAc revealed that 3–5% of DMAc is lost after each usage cycle while its effectiveness to dissolve the HERS remains equivalent to the pure DMAc. The dissolution of HERS ensures the liberation of copper cladded on the surface of WPCBs, and thus the proposed process avoids the requirement of highly energy intensive metal liberation processes. © 2016 Elsevier Ltd